Since their vertices have the same x-value , solving their derivative equal to zero must give the same answer:
A & D are eliminated:
The derivative of h(x) in A is 2x+24
h'(x)=0 g'(x)=0
2x+24=0 2x=0
x=-12 x=0
Similarly the derivative of h(x) in D is 2x-24
h'(x)=0 g'(x)=0
x=12 x=0
Knowing that B & C give the same x-value when solving for the derivative=0
We know that the only difference comes down to the y-value when substituting x=0 in h(x).
The y-value of the vertex of h(x) must be +12 the y-value of the vertex of g(x).
We have to add 12 to get to the x-value, which means that the third option or C is your answer.